Conservation and sustainable development in a VUCA world: the need for a systemic and ecosystem‐based approach - Axel Schick (Taylor & Francis Group, 2017)
Targeting the maintenance of functional ecosystems that provide the significant basis for human well‐being is an integral part of an ecosystem‐based sustainable development. Underlying causes of ecosystem degradation such as global climate change and ever‐growing human demands that rapidly shift socioeconomic and political baselines are often unmanageable at a local scale and require a new approach to planning and action in ecosystem management. The framework conditions that challenge sustainable development are shaped by increasing Volatility, Uncertainty, Complexity, and Ambiguity (VUCA concept). Using the MARISCO method (adaptive management of vulnerability and risks at conservation sites), we analyzed 22 conservation sites, covering 26 protected areas and six administrative areas on four different continents and involving 524 participants. VUCA conditions were present across cultures and biomes, yet the responses in planning and management varied among conservation sites. The findings of both the qualitative and quantitative analyses confirm that participants understand how far human well‐being heavily depends on the functionality of ecosystems that were seen to suffer from a wide range of stresses and threats of varying criticality. Worldwide, local stakeholders and experts rated impacts of global climate change as most critical. In attempts to achieve ecosystem‐based sustainable development, most management teams strive for more risk‐robust and adaptive strategies by advocating for active risk management. A common factor identified among all case studies was the need for cooperative management between smaller conservation sites in order to address large‐scale challenges.